Role of Organic Materials and Phosphate Solubilizing Bacteria to Available Phosphate in Soil And Growth of Tomato Plant (Solanum lycopersicum) - Salifa Quratul Aini Sabrina; Aisyah Aisyah; Adinda Nurul Huda (University of Darussalam Gontor, Ponorogo, East Java Indonesia, 2020)
Tomato plant (Solanum lycopersicum) is a horticultural plant that has high economic value. The demand for tomatoes per year is an average of 20%. In order to meet the demand for tomatoes, it is necessary to increase tomato production both in quality and quantity. This study aims to determine the effect of the use of phosphate solubilizing bacteria (BPF), the use of organic matter, and the effect of the interaction of phosphate solubilizing bacteria (BPF) and organic matter on soil pH, soil available P, the number of P solvent microbial populations and the growth of tomato plants. The design used in this study was a factorial Completely Randomized Design (CRD) consisting of 2 factors, namely the first factor was the concentration of Pseudomonas sp. which consists of 3 levels, namely without giving the bacteria Pseudomonas sp. (P0), giving the bacteria Pseudomonas sp. 10 ml (P1), and giving the bacteria Pseudomonas sp. 20 ml (P2). The second factor was the provision of organic material in the form of goat manure dosage consisting of 2 levels, namely without organic material (B0), and with organic material of 100 gr / polybag (P1). The parameters observed were plant height growth, number of leaves, shoot wet weight, crown dry weight, number of flowers, available soil P, soil pH, and the total population of soil P solubilizing microbes. The results showed that there was an interaction between the inoculum of Pseudomonas sp. and organic matter affects the growth of plant height, number of leaves, shoot wet weight, crown dry weight, number of flowers, available soil P, soil pH, and total soil P solvent microbes